Program Tahfidz al-Qur’an di Pondok Pesantren Darul Qur’an Sumbersari Kediri - rizki oktaviana (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
Darul Qur’an Islamic boarding school is one of the Islamic boarding schools. Still in the same scope as pesantren Darussalam Sumbersari Kencong Kepung Kediri This pesantren was founded in 1992 under the care of KH Abi Musa Al-Asy’ari He is one of the sons-in-law of the founder of the Islamic boarding school Darussalam (often referred to as the Sumbersari Islamic boarding school), namely KH Imam Faqih Asy’ari. Asy’ari is Mrs. Nyai Hj Maslikhah Faqih and now has a son One of which has turned to the Creator, the and daughter. He was the first year of the establishment of this pesantren, the number of students was not too big many of these students even resided in his residence. The method used in the Darul Qur’an boarding school is temporary. This did not exist until now and recently the Darul Qur’an Islamic boarding school. Will apply the method of memorizing As for the procedures for reading it with tartil, tartil is reading slowly according to mad or length in short, what has been studied in the Tajweed books at diniyah schools Sumbersari. Tajweed knowledge is knowledge created to determine the granting of rights letters, such as mad and character, besides that there is also tarqiq. Is to reach the peak of the improvement of al-Qur’an lafadz